Dinoderus minutus and D. breνis (Coleoptera: Bostrychidae): Two Exotic Wood Borers Introduced to Greece - Buchelos, C.TH. (ENTOMOLOGIA HELLENICA, 1991)
Two Bostrychidae species, Dinoderus minutus (Fabricius) and D. brevis Horn, found infesting bamboo articles – imported from Hong Kong and the Philippines respectively – in the region of Athens, are reported as new records from Greece. Information about their distribution and hosts is provided; furthermore their economic importance for Greece is examined.